2008
DOI: 10.4161/cc.7.8.5723
|View full text |Cite
|
Sign up to set email alerts
|

HSP90: The Rosetta stone for cellular protein dynamics?

Abstract: The Hsp90 proteomic network is expansive and includes a variety of cell processes operating within the cytoplasm and nucleoplasm. Though the functional significance of the extensive interactions has not been defined, we suggest that the Hsp90 molecular chaperone machinery promotes dynamic behaviors for client proteins that is critical to achieve homeostasis. A general rapid action by cell factors would permit both proper assembly of biological complexes and efficient transitions between distinct structures. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 67 publications
4
54
0
Order By: Relevance
“…34 In support of this hypothesis, we observed that activation of PIDD is associated with Hsp90 release and that nuclear PIDD enriched in signallingcompentent PIDDosomes does no longer interact with Hsp90. In addition to the release of Hsp90 upon PIDD activation, we provide evidence that the Hsp90/PIDD interaction before activation is required for the function of PIDD in NF-kB and caspase-2 activation.…”
Section: Discussionsupporting
confidence: 72%
“…34 In support of this hypothesis, we observed that activation of PIDD is associated with Hsp90 release and that nuclear PIDD enriched in signallingcompentent PIDDosomes does no longer interact with Hsp90. In addition to the release of Hsp90 upon PIDD activation, we provide evidence that the Hsp90/PIDD interaction before activation is required for the function of PIDD in NF-kB and caspase-2 activation.…”
Section: Discussionsupporting
confidence: 72%
“…The hormetic effect induced by Hsp90 inhibitors may be of advantage in this regard because it potentially affects many of the pathways mediated by Hsp90, its cochaperones and the ever growing list of client proteins (Camphausen and Tofilon 2007, Dezwaan and Freeman 2008, Jarosz and Lindquist 2010.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the core molecular chaperone machinery, including Hsp70 and Hsp90, has been suggested to take primary responsibility for maintaining a dynamic cellular environment (23,41) by taking part in transient low affinity protein-protein interactions (25). In addition some members of this group, most notably Hsp90, have more selective roles binding preferentially to specific classes of already folded proteins (42).…”
Section: Hsp90 Regulation Of Irf-1 Is Mediated By Hsp70mentioning
confidence: 99%